(untitled) (Global Journal of Management and Business Research, 2023)
The purpose of this study is to examine the role of human resource management practices on organizational innovation. This study is examined through the lens of Dynamic capability Theory. The methodological approach of this study is a review of literature to identify determinants of organizational innovation. Furthermore, this study ventures into an in-depth analysis of each determinant from which propositions are formulated. Findings of this study show that human resources practices consisting of organizational restructuring, organizational culture, job redesign, managerial leadership and human resource planning are key practices associated with organizational innovation. Thus, this study argues that to confront the challenges associated with the ever-evolving nature of the external environment, top management must use HRM practices to support and drive organizational innovation. So, apart from developing employee competencies and commitment, human resource management contributes to driving organizational innovation. This study extends the literature by supporting the notion of dynamic capabilities theory that innovative driven human resource practices enable regeneration and the creation of new firm’s resources. This study is limited by only assessing the role of human resource practices in innovation driven organizational innovation.